2021
DOI: 10.3389/fmed.2021.725387
|View full text |Cite
|
Sign up to set email alerts
|

Short 2-[18F]Fluoro-2-Deoxy-D-Glucose PET Dynamic Acquisition Protocol to Evaluate the Influx Rate Constant by Regional Patlak Graphical Analysis in Patients With Non-Small-Cell Lung Cancer

Abstract: Purpose: To test a short 2-[18F]Fluoro-2-deoxy-D-glucose (2-[18F]FDG) PET dynamic acquisition protocol to calculate Ki using regional Patlak graphical analysis in patients with non-small-cell lung cancer (NSCLC).Methods: 24 patients with NSCLC who underwent standard dynamic 2-[18F]FDG acquisitions (60 min) were randomly divided into two groups. In group 1 (n = 10), a population-based image-derived input function (pIDIF) was built using a monoexponential trend (10–60 min), and a leave-one-out cross-validation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…However, it may introduce errors into the parametric analysis as it does not take into account the specificity of the individual IF [ 20 ]; (ii) two-short-dynamic-scanning, which requires two separate scans after 18 F-FDG injection, such as (0-6 min + 60-75 min) scans, (0-10 min + 55-60 min) scans, (0-10 min + 40-60 min) scan and two 5-min scans [ 21 25 ]. These studies showed that the generated parameter metabolic rate of glucose (MR glu ) [ 21 ] or Ki [ 22 , 24 , 25 ] is highly correlated with the reference parameter calculated from the full scan. However, such a protocol requires a break in the middle, and the problem of image registration can limit the feasibility; and (iii) only early-time scanning, with dynamic analysis carried out based on the acquired data from the early frames, such as 0-30 min scans.…”
Section: Introductionmentioning
confidence: 99%
“…However, it may introduce errors into the parametric analysis as it does not take into account the specificity of the individual IF [ 20 ]; (ii) two-short-dynamic-scanning, which requires two separate scans after 18 F-FDG injection, such as (0-6 min + 60-75 min) scans, (0-10 min + 55-60 min) scans, (0-10 min + 40-60 min) scan and two 5-min scans [ 21 25 ]. These studies showed that the generated parameter metabolic rate of glucose (MR glu ) [ 21 ] or Ki [ 22 , 24 , 25 ] is highly correlated with the reference parameter calculated from the full scan. However, such a protocol requires a break in the middle, and the problem of image registration can limit the feasibility; and (iii) only early-time scanning, with dynamic analysis carried out based on the acquired data from the early frames, such as 0-30 min scans.…”
Section: Introductionmentioning
confidence: 99%